Prevalencia de nefropatía en el paciente portador de virus de inmunodeficiencia humana en el servicio de infectología del Hospital Rafael Ángel Calderón Guardia de enero a diciembre 2017 - Arley Vargas, Diego Armando (2019)
HIV infection is highly prevalent worldwide. Renal disorders, both acute and chronic, are more common in patients with HIV than in the general population, being present in up to 30% of these patients. Patients with HIV infection can develop various glomerular, vascular, tubulointerstitial and obstructive nephropathies related in some cases to the virus itself, to the drugs administered or to the coinfections they present. Given this, it is important to determine the prevalence of nephropathy in patients with HIV in the health center. Objective: to determine the prevalence of patients with nephropathy in the HIV carrier population treated at the RACG Hospital. Population: patients in the infectology department Rafael Ángel Calderón Guardia Hospital. Methods: observational, retrospective study. A prevalence of 20% patients with chronic kidney disease of KDIGO 2 or more stages is documented; 2.5% of the population presented significant proteinuria unrelated to viral load or CD4 count. It is necessary to improve the control for the prevention and / or diagnosis of nephropathy in the patient with HIV in the infectology department of H. R. A. C. G.